Prevalence and Correlates of Discomfort and Acceptability of Acupuncture among Outpatients in Chinese Acupuncture and Moxibustion Departments: A Cross-Sectional Study. (24th June 2013) - Liu, Baoyan; Xu, Huanfang; Guo, Shengnan; Wu, Jiani; Liu, Jia; Lim, Min Yee; Liu, Zhishun
Abstract : Objective. This study aims to give a profile of discomfort and acceptability of acupuncture, including the prevalence and association with demographic and acupuncture-related factors. Methods. A cross-sectional study was conducted in Beijing, China. Outpatients of acupuncture and moxibustion departments were recruited using purposive sampling. 925 subjects were interviewed with an anonymous questionnaire. Multinomial and binary logistic regression were used to analyze factors affecting discomfort and acceptability of acupuncture. Results. The average VAS value of 925 subjects' acupuncture discomfort was 2.66 ± 2.02, within the range of mild discomfort. Acupuncture was easily accepted by 81.1% of the subjects. Results of logistic regression were as follows: (1) subjects with a better knowledge of acupuncture, or a greater fear of pain or needles, experienced more "moderate to severe discomfort" and showed a decreased acupuncture acceptance (P < 0.001 or P < 0.01 ); (2) Acupuncture with less discomfort or implemented by a more qualified doctor was easy to be accepted (P < 0.001 ); (3) subjects aged 20–29 preferred to report "moderate to severe discomfort" while those aged 40–59 preferred to report "slight discomfort" (P < 0.001 ). Conclusion. Acupuncture is an acceptable therapy with less discomfort, which can be greatly affected by fear of pain or needles, age, knowledge of acupuncture, and professional title of acupuncturist.